Investigation of the van der waals interactions in a Bose-Einstein condensate via electromagnetically-induced transparency - Mohan, Anushyam (2013)
This thesis focusses on the development of the experimental system used to study the eff ect of Rydberg blockade interactions in clouds of ultracold atoms and quantum degenerate gases. Initial measurements have been performed quantifying these interactions, like the Rydberg blockade radius and its variation with the density of sample, which can be very useful in devising eff cient systems for quantum information processing in quantum gates and/or as probes for detecting impurities in a sample as has been recently proposed [1]. The e ffects of the Rydberg atom interactions are probed via electromagnetically-induced transparency (EIT). The experimental system and apparatus required for the production and detection of ultracold atoms and quantum degenerate gases is developed. Furthermore, the laser systems used for the production of Rydberg atoms via the two-photon transitions are also described. To highlight the density dependent eff ects of the Rydberg atom interactions and the unique advantages o ered to us by the Rydberg blockade eff ect, we compare the EIT experiments performed on a Λ-system using Raman lasers and the experiments performed with a ladder system involving the ground state, the fi rst excited state and a Rydberg state of Rb-87. The manifestation of the blockade eff ect with atom number density, with temperature of the atoms and with the principal quantum number of the Rydberg state to which the atoms are excited, is discussed. The usefulness of the Rydberg blockade interaction as a phenomenon to be exploited in quantum information processing and an outline of the future directions of our experiments concludes the thesis.